2020
DOI: 10.1038/s41467-020-14979-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient genome-wide interactions of the master transcription factor NLP7 initiate a rapid nitrogen-response cascade

Abstract: Dynamic reprogramming of gene regulatory networks (GRNs) enables organisms to rapidly respond to environmental perturbation. However, the underlying transient interactions between transcription factors (TFs) and genome-wide targets typically elude biochemical detection. Here, we capture both stable and transient TF-target interactions genome-wide within minutes after controlled TF nuclear import using time-series chromatin immunoprecipitation (ChIP-seq) and/or DNA adenine methyltransferase identification (DamI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 56 publications
5
124
0
Order By: Relevance
“…This study also showed that those TFs are connected with additional second layer of TFs, which includes CDF1 (Varala et al, 2018). In addition, it is reported that master factor NLP7 targets multiple TFs including LBD37, LBD38, TGA4, HAP2C, NAC096, and CDF1 using the TARGET system (Alvarez et al, 2020), suggesting that CDF1 is a component of the regulatory network involved in N responses. In addition, we previously reported that tomato and Arabidopsis plants overexpressing the AtCDF3 gene, the closest homolog of CDF1, exhibited changes in primary metabolism, with increased amounts of amino acids like glutamine, asparagine and GABA, and higher sucrose contents (Corrales et al, 2017;Renau-Morata et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…This study also showed that those TFs are connected with additional second layer of TFs, which includes CDF1 (Varala et al, 2018). In addition, it is reported that master factor NLP7 targets multiple TFs including LBD37, LBD38, TGA4, HAP2C, NAC096, and CDF1 using the TARGET system (Alvarez et al, 2020), suggesting that CDF1 is a component of the regulatory network involved in N responses. In addition, we previously reported that tomato and Arabidopsis plants overexpressing the AtCDF3 gene, the closest homolog of CDF1, exhibited changes in primary metabolism, with increased amounts of amino acids like glutamine, asparagine and GABA, and higher sucrose contents (Corrales et al, 2017;Renau-Morata et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…In addition, recent studies point to an involvement of CDF1, the closest CDF3 homolog, in the responses to nitrogen (Varala et al, 2018). Moreover, it is reported that NLP7, a master regulator of the nitrogen signaling pathway, targets multiple TFs including CDF1 (Alvarez et al, 2020), suggesting that CDF1 plays a role in the regulatory network involved in N responses. However, there is still a lack of information regarding the specific roles of CDF1 and CDF3 in N responses.…”
Section: Expression Of Cdf3 Gene In Response To N Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, transcriptome analysis of the Arabidopsis nlp7 (from a different orthogroup than NIN ) mutant shows altered expression levels of several genes encoding NF-YA subunits, including AtNF-YA2 and AtNF-YA10 [ 69 , 70 ]. This suggests that (some) NLPs can regulate the expression of NF-Y (A1) .…”
Section: Function Of Nin: Acquired Upon Recruitment or Adopted Fromentioning
confidence: 99%
“…This level of induction is comparable to that in Lotus and Medicago [ 49 , 67 ]. In Arabidopsis, LBD16 has been shown to be a direct target of NLP7 [ 70 ]. Therefore, NIN-controlled LBD16 expression most likely is adopted from a non-symbiotic module in which its expression is controlled by NLP, and this module evolved before the occurrence of nodulation.…”
Section: Function Of Nin: Acquired Upon Recruitment or Adopted Fromentioning
confidence: 99%